2013 IEEE Conference on Computer Vision and Pattern Recognition 2013
DOI: 10.1109/cvpr.2013.82
|View full text |Cite
|
Sign up to set email alerts
|

Poselet Conditioned Pictorial Structures

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
196
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 317 publications
(196 citation statements)
references
References 25 publications
0
196
0
Order By: Relevance
“…The images are of people in various sport poses. We use the observercentric annotations as used in [10] for training and testing. We train a full body model comprised of a 2-level hierarchy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The images are of people in various sport poses. We use the observercentric annotations as used in [10] for training and testing. We train a full body model comprised of a 2-level hierarchy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work [11,10] has shown that part detections conditioned on the location of larger composite parts improves pose estimation performance; however, these composite parts are often constructed to form tree graph structures [16]. Inspired by these recent advances, we design a hierarchical inference machine that similarly encodes these interactions among parts at different scales in the image.…”
Section: Incorporating a Hierarchymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, out of studio environments usually include dynamic background and clutter. To address these challenges, most of the recent work relies on modelling the human body from an ensemble of parts [2,3].…”
Section: Introductionmentioning
confidence: 99%